Incidência de trombose venosa profunda e qualidade de sua profilaxia em serviços de cirurgia vascular e ortopedia de Hospital Universitário terciário de Minas Gerais - Alberto Okuhara (2013)
Objective: to study the incidence of deep vein thrombosis and the quality of its prophylaxis in hospitalized patients undergoing vascular and orthopedic surgical procedures. Method: a transverse study evaluating 296 patients from clinics Vascular Surgery and Orthopaedic clinic in University Hospital between March 2011 and July 2012. The incidence of deep venous thrombosis was determined by vascular ultrasonography vascular performed in all patients. The risk factors of each patient were stratified according to Caprini. We evaluated the quality of prophylaxis compared with the prophylactic measures taken to hospital and prophylaxis guidelines from the American College of Chest Physicians. Results: the mean incidence of deep venous thrombosis in groups of Vascular Surgery and Orthopaedics was 5.3% and 8.5%, respectively, and the total was 7.5%. Regarding risk groups for venous thromboembolism, 10.8% were considered low risk; moderate risk, 14.9%; 24.3%, high risk and 50.5%, highest risk. The quality of prophylaxis for venous thromboembolism was adequate in 57.7%. In the group of Vascular Surgery, appropriate prophylaxis was 52.9% and in the group of Orthopedics was 68.0%. Adequate prophylaxis rates were 72.2% and 71.6% in the groups of high and highest risk, respectively. As for prophylaxis in groups of low and moderate risk, the rates were 31.3% and 6.8%, respectively. Excessive use of prophylaxis was seen in 68.7% and 61.4% in the low and moderate risk, respectively. Conclusion: the incidence of deep venous thrombosis of 7.5% in Vascular Surgery and Orthopaedics Clinic was similar to the literature. Most patients have high and highest risk for deep venous thrombosis prophylaxis and needs. However, in daily medical practice, there is still deficiency in the quality of prophylaxis. There is need to recognize the situation of daily practice to be taken measures to prevent sequelae and death by deep vein thrombosis.